HDAC4 Is Indispensable for Reduced Slow Myosin Expression at the Early Stage of Hindlimb Unloading in Rat Soleus Muscle - Inna I. Paramonova; Natalia A. Vilchinskaya; Boris S. Shenkman (MDPI AG, 2021)
It is well known that reduced contractile activity of the main postural soleus muscle during long-term bedrest, immobilization, hindlimb unloading, and space flight leads to increased expression of fast isoforms and decreased expression of the slow isoform of myosin heavy chain (MyHC). The signaling cascade such as HDAC4/MEF2-D pathway is well-known to take part in regulating MyHC I gene expression. Earlier, we found a significant increase of HDAC4 in myonuclei due to AMPK dephosphorylation during 24 h of hindlimb unloading via hindlimb suspension (HU) and it had a significant impact on the expression of MyHC isoforms in rat soleus causing a decrease in MyHC I(β) pre-mRNA and mRNA expression as well as MyHC IIa mRNA expression. We hypothesized that dephosphorylated HDAC4 translocates into the nuclei and can lead to a reduced expression of slow MyHC. To test this hypothesis, Wistar rats were treated with HDAC4 inhibitor (Tasquinimod) for 7 days before HU as well as during 24 h of HU. We discovered that Tasquinimod treatment prevented a decrease in pre-mRNA expression of MyHC I. Furthermore, 24 h of hindlimb suspension resulted in HDAC4 nuclear accumulation of rat soleus but Tasquinimod pretreatment prevented this accumulation. The results of the study indicate that HDAC4 after 24 h of HU had a significant impact on the precursor MyHC I mRNA expression in rat soleus.